Fungos deteriorantes de empanados congelados de frango: isolamento, caracterização e crescimento em baixas temperaturas - Saccomori, Fernanda (2013)
Consumption of frozen chicken breaded has increased considerably in recent decades, since they are practical and tasty, able to meet the needs of consumers. The intrinsic characteristics of this product are favorable to the proliferation of pathogenic and spoilage micro -organisms and the application of low temperatures has been the method used to extend the life of these breaded meat. Microbiological contamination can originate in breaded raw material used for production or produced during the handling and processing operations and multiplication of these microorganisms during storage can modify the sensory and nutritional properties of the food, and pose a problem food security. Due to their ability to overcome barriers of temperature and water activity, fungi are the main micro -organisms able to degrade the group of frozen foods, which, besides the appearance and deteriorating economic losses, represents a public health problem by the possibility production of mycotoxins in the product and consumer exposure. The aim of this study was to identify the main species of filamentous fungi involved in the deterioration of frozen chicken breaded , check secondary metabolites produced by the same and assess the growth of the two predominant species when exposed to low temperatures and, in parallel, to determine the temperature at counters freeze 6 supermarkets in the city of Santa Maria - RS. The predominant species involved in the deterioration of frozen chicken breaded were Penicillium glabrum, Penicillium polonicum, Penicillium manginii, Penicillium solitum and Penicillium crustosum. The analysis of the secondary metabolite profile showed the capacity to synthesize mycotoxins as cyclopiazonic acid citroviridina, roquefortina C, penitren A and verrucosidina by some isolates. The results demonstrated that the fungus P. polonicum, was able to form visible colonies on the surface of frozen chicken breaded kept at -5°C for 120 days. For P. glabrum the lowest growth was observed that temperature was 0°C. A ' spot ' supermarkets temperature analysis revealed temperature higher than -5°C in at least one of the time points evaluated, and 4 supermarkets 6 (66%) had at least one peak temperature above 0°C, with a maximum of 9.8 °C. Since there is occurrence of storage temperatures at which frozen foods fungi P. polonicum and P. glabrum could develop and knowing that these species have the ability to produce toxic metabolites, emphasize the need for greater attention to research related to fungal spoilage of frozen foods, source of contamination, methods of prevention and possible implications of the consumption of contaminated for public health products.